2019
DOI: 10.29121/granthaalayah.v7.i4.2019.930
|View full text |Cite
|
Sign up to set email alerts
|

Needle Stick Injuries Among Dental Students in Ishik University Faculty of Dentistry and Hawler Medical College

Abstract: Background and objectives: Needle stick injuries pose a high risk to health care workers including dental students. They represent a major risk factor for transmitting blood borne pathogens including hepatitis B virus, hepatitis C virus and human immunodeficiency virus. Needles of syringes are the most commonly identified sharp object causing the injuries. Therefore, this study conducted to determine the prevalence of needle stick injuries among dental students in Ishik university facualty of dentistry and Haw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…After an injury, 77.2% (n=44) of our study participants cited that they washed their hands with soap and water with a significantly higher percentage of them having a satisfactory mean awareness score. Similarly, 85.2% of students in Iraq washed their wounds with soap and water [ 10 ]. On the other hand, an Indian study of dental students found that only 12% of injured students washed the site injury with soap and water immediately after the injury [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an injury, 77.2% (n=44) of our study participants cited that they washed their hands with soap and water with a significantly higher percentage of them having a satisfactory mean awareness score. Similarly, 85.2% of students in Iraq washed their wounds with soap and water [ 10 ]. On the other hand, an Indian study of dental students found that only 12% of injured students washed the site injury with soap and water immediately after the injury [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dental students and trainees are the groups most vulnerable to sharps injury due to the nature of dental training in different departments during the clinical sessions to complete their clinical requirements. Additionally, dental assistants are also among the higher-risk groups as they are delegated to provide chair-side support during the various steps of dental treatment in addition to preparing instruments and equipment for dental procedures and maintaining clinics’ environments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%